Physicochemical and functional properties of dried okra (Abelmoschus esculentus L.) seed flour - Ofori, Jemima; Tortoe, Charles; Agbenorhevi, Jacob K. (Food Science & Nutrition, 2024)
This is an article published in Food Science & Nutrition 2020;8:4291–4296. DOI: 10.1002/fsn3.1725